2018
DOI: 10.24042/djm.v1i3.3238
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Taksonomi Bloom Revisi untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis

Abstract: The ability to understand students' concepts is important. But the ability to understand the concept of students does not grow without just passing on an action from a serious educator in dealing with this problem. Developing learning objectives in general is one of the right steps taken by educators in learning. Bloom Revision Taxonomy that researchers will use in developing learning objectives in this study. so this study aims to describe students' abilities in understanding concepts through Bloom Revision's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
7
0
8
Order By: Relevance
“…So learning activities based on Revised Bloom's Taxonomy are effective for improving problem-solving skills. Furthermore, the results of this study are strengthened by research, showed that thematic learning in the perspective of Revised Bloom's Taxonomy could make the learning process more active and meaningful for students (Ardiani et al, 2013;Netriwati, 2018;Sari et al, 2017).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…So learning activities based on Revised Bloom's Taxonomy are effective for improving problem-solving skills. Furthermore, the results of this study are strengthened by research, showed that thematic learning in the perspective of Revised Bloom's Taxonomy could make the learning process more active and meaningful for students (Ardiani et al, 2013;Netriwati, 2018;Sari et al, 2017).…”
Section: Resultsmentioning
confidence: 62%
“…The knowledge dimension is divided into 4, namely factual, conceptual, procedural, and metacognitive. In contrast, the cognitive process dimension consists of 6 dimensions, namely remembering (C1), understanding (C2), applying (C3), analyzing (C4), evaluating (C5), and creating (C6) (Effendi, 2017;Handayani, 2020;Netriwati, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembelajarannya harus tahap demi tahap mulai dari pemahaman ide dan konsep yang sederhana sampai kejenjang yang lebih kompleks. Seseorang tidak mungkin mempelajari konsep yang lebih tinggi sebelum ia menguasai konsep yang lebih rendah (Netriwati, 2018;Ningsih, 2016). Hal ini merupakan tantangan yang dihadapi oleh guru untuk menjadikan matematika sebagai sesuatu yang menarik.…”
Section: Pendahuluanunclassified
“…Agar tujuan mudah dinilai keberhasilannya, maka tujuan itu harus operasional dan terklasifikasikan dengan rinci. Taksonomi yang digunakan dalam pendidikan untuk mengklasifikasi tujuan instruksional dibagi dalam 3 domain, yakni ranah pengetahuan yang berhubungan dengan tujuan orientasi belajar, 2) ranah afektif yang berhubungan pada perasaan, sikap hati, dan emosi, 3) ranah psikomotor yang berhubungan dengan kepiawaian motorik (Netriwati, 2018). Benjamin.…”
Section: Pendahuluanunclassified